Principles of quantum physics: A phenomenological study of illegal mining in the construction of social justice - Widiatmoko, Dekki; Saputra, Dedi; Jubaidi, Didi (Universitas Sultan Ageng Tirtayasa, 2024)
Illegal mining, better known as illegal mining, is a complex multidimensional problem. This study uses a phenomenological lens to explore the deep meaning of the experiences of illegal mining actors in the Merangin Regency, Jambi. The findings of this study consistently show that severe economic pressures, combined with limited access to education and job opportunities, are the main drivers of community involvement in illegal mining activities. Informants explicitly stated that they knew their actions' legal and environmental implications but felt trapped in a difficult situation. By adopting a quantum physics lens, this study emphasizes that individuals, like subatomic particles, are often in a state of superposition between various choices, trapped in moral and economic dilemmas. This approach offers an innovative analytical framework for understanding the complexity of contemporary social problems. To overcome this problem, comprehensive efforts involve expanding economic opportunities, developing community capacity, and enforcing fair and community-friendly laws. Overall, this study highlights the importance of understanding the social and economic contexts that underlie community involvement in illegal mining activities. By adopting an interdisciplinary approach combining qualitative methods and quantum physics concepts, this study significantly contributes to developing more effective policies and intervention programs in addressing this problem.